Varicela en un hombre de 33 años - María Carolina Rojas-Saavedra (Asociación Colombiana de Infectología, 2021)
We describe a case of varicella in one immunocompetent man of 33 years, who consulted by cutaneous lesions consistent in maculopapular and vesicles generali-zed after 10 days of evolution, accompanied by fever and conjunctivitis. Diagnosis of varicella was confirmed by direct stain and biopsy with immunohistochemistry analysis. The patient improved without antiviral treatment and no complications. We consider this caes of interest because its inusual presentation in one man without immunodeficiency nor subjacent disease. We reviewed the situation of varicella in Colombia and of the vaccination programs.